Lipid Variables Related to the Extent and Severity of Coronary Artery Disease in Non-Diabetic Turkish Cypriots - Cenk CONKBAYIR; Burak AYÇA; E. Baris ÖKÇÜN (Tehran University of Medical Sciences, 2015)
Background: We aimed to analyze the association between lipid variables and the extent and severity of coronary artery disease (CAD) in non-diabetic Turkish Cypriots. Methods: Overall, 412 patients (mean (SD) age: 58.8 (10.5) yr, 50.1% male) who underwent diagnostic coronary angiography were included in this single-center, cross-sectional study. The Friesinger index (FI) was used to assess the extent and severity of CAD. The lipid variables [total cholesterol, LDL-c, HDL-c, triglyceride (TG) levels and the TG/HDL-C ratio] were categorized into quartiles and evaluated regarding extensive/severe CAD. Potential risk factors in the Turkish Cypriot cohort were evaluated as predictors of CAD in univariate and multivariate logistic regression models. The population of this study are non-diabetic Turkish Cypriots which are administrated North Cyprus. Results: The mean (SD) Friesinger index was 6.9 (4.4), and 59.0% of the patients exhibited a Friesinger index category of ≥5. In the univariate analysis, extensive/severe CAD was directly related to total triglycerides (P=0.01) and TG/HDL-c quartiiles (P=0.001) and inversely related to HDL-c quartiles (P=0.001). In the multivariate model, diabetes (OR: 4.9; 95% CI: 1.3 - 19.2; P=0.02), male gender (OR: 3.1; 95% CI: 0.95 - 10.3; P=0.06) and high TG/HDL-c ratio (OR: 2.2; 95% CI: 1.3 - 3.8; P=0.004 in the overall population and OR: 1.9; 95% CI: 1.4 - 2.3; P=0.003 except diabetics) were the significant predictors of CAD. Conclusion: We found a significant relationship between the lipid quartiles and the extent and severity of CAD based on the Friesinger index. Male gender, co-morbid diabetes and the TG/HDL-C ratio also played significant roles in predicting CAD risk in non-diabetic Turkish Cypriots.